Pustakawan Guru sebagai Agen Literasi Informasi di Sekolah Madania Parung Bogor - Azrina, Okta; Kesuma, Mezan el-Khaeri; Nurjannah, Latief (Jurnal El-Pustaka, 2022)
This paper aims to analyze the role of teacher librarians as agents of information literacy at Madania Parung Elementary School, Bogor. Librarians are information literacy agents in libraries. As the "agents", librarians have duties and responsibilities to users in information literacy. The teacher librarian as an information literacy agent has duties and responsibilities to its users, especially students to be information literate through the activities carried out. The Madania school library has a teacher librarian who can create information literate users from an early age. Therefore, this study examines the role of teacher librarians in information literacy. The research method used is qualitative with phenomenological methods. The results of the study can be seen as the teacher librarian is an information literacy agent at the Madania Parung Elementary School, Bogor. This can be seen from the three main roles of teacher librarians, namely teacher librarians as curriculum leaders; teacher librarians as information specialists; and teacher librarians as managers of information services. These three roles can be realized in activities carried out by teacher librarians, namely library classes, best readers, storytelling, and library tours by collaborating with various parties, both internal to the school and externally through collaboration with schools in the Bogor environment.